TEORI NOLTING : ANALISIS KESALAHAN SISWA DITINJAU DARI GAYA BELAJAR - Layyinah, Ulfatul; Sidik, Rahmad Fajar; Ahied, Mochammad; Hadi, Wiwin Puspita; Yamin, Yamin (Natural Science Education Research, 2024)
The aim of this research is to determine students' learning styles as well as the average and types of errors based on Nolting's theory in solving light and optical instrument problems in terms of learning styles. This research uses quantitative descriptive methods. The population and sample are all class VIII students for the 2023/2024 academic year, totaling 26 people. Sampling used nonprobability sampling technique with saturation sampling type. Data collection uses tests, questionnaires and documentation. The research results show that: 1). 5 types of learning styles used by students; visual, auditory, kinesthetic, visual auditory, and auditory kinesthetic. The visual learning style is dominantly used in the classroom. 2) Average errors for types of learning styles, namely; a) The average visual learning style is 8, the type of error that is most often made is Careless Errors with 26 errors (31%). b) The average auditory learning style is 8, the type of error that is most often made is Careless Errors with 17 errors (28%). c) The average kinesthetic learning style is 10, the type of error that is most often made is Careless Errors with 15 errors (38%). d) The average visual auditory learning style is 5, the type of error that is most often made is Concept errors with 3 errors (60%). e) The average auditory kinesthetic learning style is 6, the type of error that is most often made is Concept errors with 6 errors (50%).